Analisis Yuridis Pengembangan Usaha Bahari Masyarakat Pesisir Berbasis Blue Economy di Kelurahan Kolo Kota Bima - Nuratika; Ridwan; Nasrullah (Institut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to determine the regulations governing marine businesses and Blue Economy in Indonesia and analyze the implementation of marine business development for coastal communities based on Blue Economy in Kolo Village, Bima City. This research uses normative legal methods with statutory and conceptual approaches to analyze regulations and legal values related to blue economy-based marine business development in Kolo Village. Data is sourced from primary, secondary, and tertiary legal materials, which are collected through systematic literature studies to answer problem formulations. The results show that the development of the marine sector in Kolo Village, which adopts blue economy principles, has a solid legal basis, both nationally through Law No. 32/2014 and internationally through UNCLOS and SDGs. The region holds strategic potential in three main areas: environmentally friendly fisheries, marine tourism and the marine product processing industry. However, implementation is still faced with structural constraints such as regulatory complexity and limited human resources. Achieving sustainable development in the region requires a comprehensive collaboration that integrates three fundamental elements: environmental protection, strengthening the local economy and structuring the legal system. This holistic approach will create an ideal coastal management model - capable of improving the welfare of local communities while ensuring the preservation of marine resources for the future. Kolo Village has the potential to become a model for implementing ecologically sound and socially just marine development concepts.